GC Insights: The Anthro-Pokécene – environmental impacts echoed in the Pokémon world - L. J. Alcott; L. J. Alcott; T. Maavara (Geoscience Communication)
Public perception of anthropogenic environmental impacts, including climate change, is primarily driven by exposure to different forms of media. Here, we show how Pokémon, the largest multimedia franchise worldwide, mirrors public discourse in the video games' narratives with regard to human impacts on environmental change. Pokémon demonstrates a trajectory towards greater acknowledgement of climate change and anthropogenic impacts in each released game and presents a hopeful vision for how society can adapt.